5PSQ-151 Optimisation of the subcutaneous administration of daratumumab. (23rd March 2022) - Ammor, W; Chapron, P; Goubil, A; Fronteau, C; Peyrilles, E; Cormier, N
Abstract : Background and importance: Daratumumab, now indicated for first-line treatment of multiple myeloma, has been available in a formulation for subcutaneous (SC) injection since April 2021. SC administration must be carried out continuously over 5 min. However, nurses who work in the hospital day care report musculoskeletal disorders, preventing continuous infusion and thus leading to drug misuse. The increase of 55% between 2020 (IV) and 2021 (SC) of the preparation volumes of daratumumab for the period from 15 May to 15 September contributes to the challenge of this project. Aim and objectives: Determine an optimal and safe setup for subcutaneous administration. Material and methods: We carried out a market study by contacting hospitals and laboratories and analysing technical data sheets to preselect a general assembly. We established a working group (2 nurses, 1 pharmacy technician and 2 pharmacists) to evaluate a suitable subcutaneous medical device according to these criteria: diameter and length of canula, dead volume, biocompatibility, cost and supplier, right use, fixation of medical device, practicality of nurses, security of nurses, feasible purging. Results: The use of an electric syringe pump (ESP) is essential for the setup. A 20 ml syringe compatible with ESP is filled with 15 ml daratumumab. A three-way flush valve for the extension tube is attached. A pre-filled syringe of 10 ml NaCl is used for flushing. Several medical devices have been evaluated: a microperfuser, an infusion kit, an epicranial needle, a hypodermic needle and a secure hypodermic needle. As a result, the microperfuser met all the selected criteria except for the cost, which is why we chose it. Finally, the total cost of administration increased from €1.23 to €5.53, this means an additional cost of €7272 for the hospital per year. Conclusion and relevance: This multidisciplinary work has allowed us to choose a subcutaneous administration setup for an anticancer treatment. Despite the additional cost, this setup combines proper use and safety and will be proposed for evaluation in the hospital day care very soon. As part of the improvement of the quality of life at work for nurses, occupational medicine is collaborating on this project. References and/or acknowledgements: Conflict of interest: No conflict of interest